Tabata Training on Improving Physical Fitness (Vo₂Max, Muscle Fitness, and Body Composition) of Female Futsal Athletes - Sugianto Purnomo Mainaki; Himawan, Agus; Haryo Mukti Widodo; Putri P, Septyaningrum; Yuli Handayani, Heni; Ghulam Zaky (Universitas PGRI Palembang, 2025)
This study aims to examine the effects of Tabata Training on improving athletes’ physical fitness, assessed through VO₂max, muscular fitness, and body composition. A quasi-experimental method with a one-group pretest-posttest design was employed. The subjects consisted of 20 athletes futsal female aged 18 to 23 years who participated in a six-week training program. Data were analyzed using statistical tests to determine differences between pre- and post-intervention measurements. The results indicated that Tabata Training had a significant effect on increasing VO₂max, muscular strength and endurance, as well as reducing body fat percentage. In conclusion, Tabata Training can be considered an effective method for enhancing athletes’ overall physical fitness.